Implementation of Jigsaw Technique to Improve Student Engagement in Writing Class - Putra, Albertus Ronny Rizal Anggoro Octavin Asmara; Tamah, Siti Mina; Prijambodo, V. Luluk; Pramono, Y. G. Harto; Budiono, Davy (Universitas Katolik Widya Mandala Surabaya, 2024)
The Jigsaw technique is an interactive teaching strategy that promotes active learning and collaboration among students. It is particularly effective in fostering engagement and improving writing skills. This study explores the effectiveness of the Jigsaw technique in enhancing student engagement and improving writing skills. Grade 8 students from a junior high school in Sidoarjo, Indonesia, were purposefully chosen for a Classroom Action Research (CAR) approach. Data collection involved pre/post-surveys, observation checklists, Focus Group Discussions (FGDs), and writing samples assessed with a standardized rubric. A mixed-methods approach, combining thematic analysis and descriptive statistics, was employed. The research design consists of iterative CAR cycles, implementing the Jigsaw technique, collecting data, and reflecting/modifying instructional strategies. Initial findings indicated below-average writing performance, prompting the need for improvement. Despite challenges in the initial cycle, adjustments in Cycle 2 led to significant improvements, surpassing passing grades. The post-survey and statistical analysis demonstrated a 57% positive impact on student engagement. FGD revealed varied opinions, but students acknowledged the motivating effects of the Jigsaw technique. The findings support the Jigsaw technique's potential to improve student engagement and writing performance. Future research could involve larger and more diverse groups to gain a more comprehensive understanding. By incorporating these insights, educators can effectively implement the Jigsaw technique to create engaging learning environments that promote collaboration, communication, and writing skill development.